Patterns of adult and youth inpatient admissions before and after the COVID-19 pandemic in a psychiatric ward: an observational study - Carolina Alves Rodrigues; Nuno Rodrigues; Miguel Nascimento; Joana Oliveira-Silva (BMC, 2022)
Abstract Background The current pandemic situation led to deep changes not only in social relationships, but also on clinical care and access to healthcare facilities. The authors aimed to understand whether this context affected the main characteristics of psychiatric hospitalizations, measured by admissions in a portuguese acute psychiatric ward. Methods Retrospective data collection of all patients admitted in Centro Hospitalar Psiquiátrico de Lisboa, in two different time periods: pre-COVID-19 (march 11th, 2019 to march 10th, 2020, n = 1845) and COVID-19 (march 11th, 2020 to march 10th, 2021, n = 1278); comparing the number of total admissions, compulsory ones, age, sex, median days of admission, median days to readmission and diagnosis at discharge. Distribution of disorders in both groups, as well as in compulsory admissions were also evaluated. The same comparisons were evaluated in the 15-25-year-old patient group. Results Statistical significance was found regarding total number of admissions (reduction of around 30.7%), as well as compulsory ones (reduction of 14%, although the relative frequency had increased), days of admission and distribution between admissions (with lower reductions regarding dementias, schizophrenia and affective disorders, while substance use disorders and intellectual disabilities presented reductions of over 50%), with no differences between gender, median age, previous admissions or readmissions. Distribution between compulsory admissions did not present differences before and during COVID periods. For patients between 15 and 25 years of age, statistical significance was found regarding total number of compulsory ones (94 versus 44, p-value = 0.01), and in all groups of diagnoses (all with p-value = 0.001). Conclusions While there was a general reduction in the overall number of patients admitted, in the most severe conditions (compulsory admissions and schizophrenia diagnosis) did not present such a reduction. Difficulties in social, clinical and family networks can explain the reduction of the time to readmission. Future research could show whether there is a rebound increase number of admissions in the other diagnoses. Trial Registration The current study was approved by the hospital's scientific and ethics committees (CCP number 0060/2021 and CES 09/2021).